2015
DOI: 10.1016/j.drugalcdep.2015.06.030
|View full text |Cite
|
Sign up to set email alerts
|

ADAPTA: A pilot randomised controlled trial of an alcohol-focused intervention versus a healthy living intervention for problem drinkers identified in a general hospital setting

Abstract: HighlightsNo evidence of a difference in AUDIT score was seen between treatments at 6 months.A greater proportion in the healthy living group attended all 4 treatment sessions.Recruitment and follow up proved challenging with this non-help seeking group.Further thought needed regarding engaging problem drinkers in a hospital setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…The present study confirms prior studies hinting that hospitalized patients suffering from AUD may not be able or ready to consider specialized treatment for their drinking problem (11). In this study, we found that the narratives told by the six participants were strikingly alike with regard to their perspectives on alcohol use, their strivings to gain control over their alcohol use, their perceptions of health-related issues as well as relatives and relations as facilitators in obtaining what was strived for, their conceptions of alcohol treatment not being an offer for them, and their feelings towards wanting to deal with their alcohol (non)issues independently.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The present study confirms prior studies hinting that hospitalized patients suffering from AUD may not be able or ready to consider specialized treatment for their drinking problem (11). In this study, we found that the narratives told by the six participants were strikingly alike with regard to their perspectives on alcohol use, their strivings to gain control over their alcohol use, their perceptions of health-related issues as well as relatives and relations as facilitators in obtaining what was strived for, their conceptions of alcohol treatment not being an offer for them, and their feelings towards wanting to deal with their alcohol (non)issues independently.…”
Section: Discussionsupporting
confidence: 87%
“…It is well-known that hospital staff has been reluctant to systematically screen for and address risky alcohol use among patients (10). Even studies that made use of outreach visits, where therapists from the AUD clinic talked to the patients at the hospitals, did not identify a large effect on treatment-seeking (9,11).…”
Section: Introductionmentioning
confidence: 99%
“…Also, it may have been due to the participation rate being lower than expected, based on participation rates in other studies conducted in the same setting. In alcohol treatment and research, it is a common challenge to recruit and maintain patients for studies, as well as for treatment [ 48 ]. Unwillingness to participate in research studies has been reported as becoming more and more common [ 36 ], especially regarding studies performed over the Internet [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…24 However, whilst this is an acceptable approach, evidence on the effectiveness of multiple health behaviour change interventions for reducing alcohol intake is limited. 25,26 People are least likely to want to change their drinking when presented with alternative behaviours in the NHS health check. 27 Furthermore, when delivered in-person, health professionals may choose to prioritise other health behaviours which they feel more comfortable discussing.…”
Section: What Is Already Known On This Topicmentioning
confidence: 99%